2012
DOI: 10.1111/j.1752-8062.2012.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Need for Academic Health Centers to Assess the Training, Support, and Career Development Requirements of Clinical Research Coordinators: Recommendations from the Clinical and Translational Science Award Research Coordinator Taskforce*

Abstract: Clinical Research Coordinators (CRCs) are a vital component of the clinical research enterprise providing a pivotal role in human subject protection through the numerous activities and responsibilities assigned to them. In 2006, the National Institutes of Health's National Center for Research resources (NCRR) implemented the Clinical and Translational Science Awards program (CTSA) to advance biomedical research. As a part of this endeavor, many workgroups were formed among the Consortium to support translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 0 publications
1
91
0
Order By: Relevance
“…These principal components closely paralleled the theoretical competency domains described by Sonstein et al for the JTF as well as those described by the Enhancing Clinical Research Professionals" Training and Qualifications group. 10,12 We scanned the structure matrix (Promax rotation; Kappa=5) to identify the most important competencies defining each component that would enable us to reduce the number of items necessary to create a shorter, more easily administered survey instrument. We identified the two highest loading items on each of the nine factors and included two additional items from the Medicines Development factor that had loadings of 0.797 and 0.792 respectively yielding a total of 20 core competencies.…”
Section: Resultsmentioning
confidence: 99%
“…These principal components closely paralleled the theoretical competency domains described by Sonstein et al for the JTF as well as those described by the Enhancing Clinical Research Professionals" Training and Qualifications group. 10,12 We scanned the structure matrix (Promax rotation; Kappa=5) to identify the most important competencies defining each component that would enable us to reduce the number of items necessary to create a shorter, more easily administered survey instrument. We identified the two highest loading items on each of the nine factors and included two additional items from the Medicines Development factor that had loadings of 0.797 and 0.792 respectively yielding a total of 20 core competencies.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons are: 1) protocols have become progressively more complex, and regulations intended to protect the safety of research subjects and study data integrity have continued to evolve; 2) as a result, the CRC's role has become more sophisticated and the CRC's responsibilities have expanded even though training programs do not cover these new responsibilities of CRCs; and 3) the additional responsibilities of CRCs place increasing burdens that could adversely affect their primary role of research subject management [2]. However, several articles suggested that only approximately half of CRCs had opportunities of training [2][3]. A warning letter by the US FDA also suggested inadequate training of CRCs [4].…”
Section: Introductionmentioning
confidence: 99%
“…A warning letter by the US FDA also suggested inadequate training of CRCs [4]. The Clinical and Translational Science Award Research Coordinator Taskforce of the US National Institutes of Health recommended that institutions conduct a gap analysis of their training program focusing on the core competencies of CRCs [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger pools of highly trained, competent professionals are needed to increase the industry's ability to safely and effectively bring new medicines to the marketplace. The necessity for further competency based education and training has been identified all over the world [10][11][12][13][14] . Many of the challenges outlined are worsened by the inability of the biopharmaceutical industry, governments and regulatory agencies, academic researchers, and the healthcare community to work together collaboratively.…”
Section: Introduction: Why Is a Systems Approach Needed?mentioning
confidence: 99%